Understanding Manner Modification from a Cross-Dependency Perspective - Norbert Corver (Languages)
This article aims to increase our understanding of the syntax of manner modification by examining it from the perspective of the syntax of anaphoric dependencies. It is proposed that the two grammatical dependencies share certain abstract formal properties and are governed by the same type of principle governing the computational system of human language. Building on the so-called IDI constraint (Inability to Distinguish Indistinguishables), it is proposed that the Computational system of Human Language (CHL) is unable to distinguish two predicates—for example, a verbal predicate and an adjectival one—if they are in a local domain. Specifically, an adjectival predicate (e.g., quick) cannot merge directly with a verbal predicate (e.g., walk). The CHL can only deal with two predicates if their linguistic environment allows them to be distinguished as different occurrences. This formal distinctness can be achieved by means of various licensing strategies, including so-called protection, which is a formal strategy that turns the modifier (e.g., quick) into a more complex syntactic object (e.g., quick+-ly). It is shown that the various morpho-syntactic implementations of the protection strategy are quite similar for Rreflexivization and for Manner Modification: (grammaticalized) body nouns, doubling pronouns, and adpositional material can be used for making the dependent element (i.e., the anaphor; the manner modifier) more complex. It is further proposed that superficially bare manner modifiers (e.g., fast) are actually complex syntactic objects, where the complexity comes from the (hidden) presence of a silent element.